1983
DOI: 10.1083/jcb.97.5.1459
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-mediated changes in gap junction structure: evidence from the low angle X-ray pattern.

Abstract: Rat liver gap junctions were isolated in Ca2+-free media and analyzed in controlled environments by x-ray diffraction of partially oriented pellets. Different treatments of the same preparations were compared. The ordered hexagonal lattices gave rise to detail that was sensitive to low Ca 2+ concentrations (0.05 mM), but not to Mg 2+ (up to 0.16 mM) or pH (between 6.0 and 8.0). The major Ca2+-mediated responses were reductions in the intensity of the (1, 0) peak and in the off-equatorial contributions to the (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 15 publications
3
39
0
Order By: Relevance
“…Electron microscopy-based structures of isolated rat liver gap junction channels showed significant differences in pore diameter between Ca 2+ and Ca 2+ -free structures (31). Atomic force microscopy of isolated murine Cx26 hemichannels showed an increase in pore diameter from 2.5 to 5 nm when Ca 2+ is removed, suggesting that Ca 2+ stabilizes the closed conformation of the channels (32).…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopy-based structures of isolated rat liver gap junction channels showed significant differences in pore diameter between Ca 2+ and Ca 2+ -free structures (31). Atomic force microscopy of isolated murine Cx26 hemichannels showed an increase in pore diameter from 2.5 to 5 nm when Ca 2+ is removed, suggesting that Ca 2+ stabilizes the closed conformation of the channels (32).…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to channels formed by connexins, which either are non-responsive to increased cytoplasmic calcium or are closed, depending on their protein composition [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that connexin hemichannels and gap junctions are sensitive to calcium environments, although the exact mechanisms of the interaction are not fully defined (Harris, 2001;Lurtz and Louis, 2007;Zhou et al, 2007b;Herve et al, 2012;Herve and Derangeon, 2013). The first observation made in the early 1980s using freeze fracture studies indicated that connexins twist the gap junction channel shut in response to supraphysiological levels of Ca 2+ (Peracchia, 1978;Unwin and Ennis, 1983;Bruzzone et al, 1996). Several studies now suggest that this may be regulated through binding of the calcium sensing subunit calmodulin.…”
Section: Physiologic Function Referencesmentioning
confidence: 99%